2011
DOI: 10.1161/hypertensionaha.110.153619
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mediates the Vascular Dysfunction But Not the Remodeling Induced by Aldosterone/Salt

Abstract: Abstract-Pathophysiological aldosterone (aldo)/mineralocorticoid receptor signaling has a major impact on the cardiovascular system, resulting in hypertension and vascular remodeling. Mineralocorticoids induce endothelial dysfunction, decreasing vasorelaxation in response to acetylcholine and increasing the response to vasoconstrictors. Activation of the epidermal growth factor receptor (EGFR) is thought to mediate the vascular effects of aldo, but this has yet to be demonstrated in vivo. In this study, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
(50 reference statements)
6
29
1
Order By: Relevance
“…NAS challenge in WT mice decreased the aortic vasodilatory response to acetylcholine (endothelium-dependent vasorelaxation; Figure 2A; Table S2) and sodium nitroprusside (endothelium-independent vasorelaxation; Figure 2B; Table S2) and increased the vasoconstrictive response to phenylephrine (a vasoconstrictor α-adrenergic agonist) as previously reported ( Figure 2C; Table S2). 22 Gene inactivation of Lcn2 did not affect vascular response to these agents ( Figure 2A; Table S2) as previously reported.…”
Section: Tarjus Et Al Ngal Mediates Mineralocorticoids Fibrotic Effecsupporting
confidence: 82%
See 2 more Smart Citations
“…NAS challenge in WT mice decreased the aortic vasodilatory response to acetylcholine (endothelium-dependent vasorelaxation; Figure 2A; Table S2) and sodium nitroprusside (endothelium-independent vasorelaxation; Figure 2B; Table S2) and increased the vasoconstrictive response to phenylephrine (a vasoconstrictor α-adrenergic agonist) as previously reported ( Figure 2C; Table S2). 22 Gene inactivation of Lcn2 did not affect vascular response to these agents ( Figure 2A; Table S2) as previously reported.…”
Section: Tarjus Et Al Ngal Mediates Mineralocorticoids Fibrotic Effecsupporting
confidence: 82%
“…22 Gene inactivation of Lcn2 did not affect vascular response to these agents ( Figure 2A; Table S2) as previously reported. 23 Therefore, NAS treatment modified the contractile phenotype regardless the Lcn2 genotype because Lcn2 inactivation had no effect on NAS-induced alterations in vascular response.…”
Section: Lcn2 Gene Inactivation Limits the Vascular Fibrosis Induced supporting
confidence: 82%
See 1 more Smart Citation
“…It has been suggested that the vascular pathological effects of aldosterone/MR result from inflammation, increased vascular reactive oxygen species, and decreased nitric oxide production (4,22,23). Such mechanisms are observed in animal models when mineralocorticoid pathway activation is associated with nephrectomy and salt excess, ischemia, or pressure overload (24,25). In the absence of associated pathology, enhanced mineralocorticoid activation per se may lead to distinct pathological events through other mechanisms that are not fully elucidated, such as ion channel remodeling (25).…”
Section: Discussionmentioning
confidence: 99%
“…7 Several lines of available evidence clearly demonstrate an important role also for endothelial cells in the response to aldosterone. 8 In this issue of the journal, Griol-Charhbili et al 9 describe their studies using an established mutant mouse to explore the role of the epidermal growth factor receptor (EGFR) in the vascular response to MR activation.…”
mentioning
confidence: 99%